Ag / Fe3O4 synergistically modified basalt fiber and PVDF composite material and preparation method thereof

By synergistically modifying basalt fibers with Ag nanoparticles and Fe3O4 nanoparticles and combining it with magnetic field orientation technology, the problem of improving the piezoelectric and electromagnetic shielding properties of PVDF-based composite materials has been solved, achieving a dual functional enhancement of the material, which is suitable for flexible electronic devices and aerospace stealth structures.

CN121159947AActive Publication Date: 2025-12-19NANJING DAMAONIU ENVIRONMENTAL PROTECTION TECH CO LTD +1

Patent Information

Application Number
CN202511685556.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-18
Publication Date
2025-12-19
Estimated Expiration
2045-11-18

AI Technical Summary

Technical Problem

Existing PVDF-based composite materials cannot simultaneously improve piezoelectric properties and electromagnetic shielding properties, failing to meet the requirements of modern electronic devices for broadband electromagnetic protection. Furthermore, traditional modification methods can damage fibers or reduce material properties.

Method used

PVDF composite materials with both high voltage electrical properties and high electromagnetic shielding effectiveness were prepared by synergistic modification of basalt fibers with Ag nanoparticles and Fe3O4 nanoparticles through multi-level modification and magnetic field-induced orientation processes.

Benefits of technology

It significantly improves the electromagnetic shielding effectiveness and piezoelectric properties of PVDF composite materials, achieving a dual functional enhancement of the material, and is suitable for flexible electronic devices, aerospace stealth structures, and intelligent electromagnetic protection equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121159947A_ABST
    Figure CN121159947A_ABST
Patent Text Reader

Abstract

The invention discloses an Ag / Fe3O4 synergistically modified basalt fiber and PVDF (Polyvinylidene Fluoride) composite material and a preparation method thereof, Ag nano particles and Fe3O4 nano particles are simultaneously modified on basalt fibers, and the limitation of a traditional single modification function is broken; the modified basalt is used for preparing the oriented PVDF composite material, so that the piezoelectric property and the electromagnetic shielding property of the prepared PVDF composite material are synchronously improved, the PVDF composite material can be directly used as a material for preparing structural parts such as equipment shells, cabins and automobiles, self-sensing and self-shielding intelligent structures are manufactured, and the PVDF composite material can be used as a novel PVDF composite material product. Good application prospects and economic values are realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of functional composite materials, in particular, to a basalt fiber and PVDF composite material modified by Ag / Fe3O4 and a preparation method. BACKGROUND

[0002] Polyvinylidene fluoride (PVDF) based composite material is a kind of composite material prepared by adding various fillers, fibers or other polymers, etc. to PVDF as the matrix. PVDF itself is an outstanding engineering plastic, which successfully achieves an excellent balance between chemical resistance, mechanical strength, processing convenience and piezoelectric effectiveness, and plays an indispensable role in modern industry and technology. However, although PVDF has good piezoelectric performance (the piezoelectric strain constant d33 of pure PVDF is 20 pC / N), its electromagnetic shielding effectiveness (Shielding Effectiveness, SE for short) is low, only 5 dB. Therefore, in the prior art, conductive fillers are often added to improve the electromagnetic shielding effectiveness of PVDF material. For example, it is reported that by introducing carbon nanotubes (CNTs) as fillers, a conductive network can be formed in the composite material, increasing the electrical conductivity of the material and effectively improving the electromagnetic shielding performance of PVDF. However, the introduction of conductive materials will destroy the ordered arrangement of PVDF molecular chains, reduce the crystallinity of PVDF, and cause the piezoelectric performance of the composite material to decrease; at the same time, the conductive network formed by the conductive material will cause the piezoelectric potential of the material to be short-circuited, which will also further cause the piezoelectric performance to decrease. In addition, it is reported that increasing the β phase content of PVDF based composite material can enhance its electromagnetic shielding performance. For example, by high-voltage polarization to make the internal charge distribution of PVDF based composite material directional rearrangement to promote the conversion of α phase to β phase, the electromagnetic shielding effectiveness can be enhanced. However, simply increasing the β phase content of the material has limited contribution to the electromagnetic shielding performance, usually <20 dB, which still cannot meet the demand of modern electronic equipment for wideband electromagnetic protection. Therefore, in order to obtain high electromagnetic shielding effectiveness, the existing PVDF based composite material has to sacrifice part of the piezoelectric performance of PVDF.

[0003] Basalt fiber (BF for short) in addition, as the preferred reinforcing body of PVDF based composite material, its surface is chemically inert, and the interface bonding between the fiber and the PVDF matrix is poor, and the stress transfer efficiency is low. Therefore, the fiber surface needs to be modified to improve the interfacial adhesion. In the traditional modification method, silane coupling agent treatment is often used to form a layer of chemical bond on the surface of the fiber to improve the interfacial bonding between the fiber and the resin matrix; but the surface of the fiber treated by silane coupling agent will form an insulating siloxane network, which will hinder the transmission of electrons, which will also reduce the electrical conductivity of the fiber.

[0004] Dopamine is a neurotransmitter that can spontaneously polymerize into polydopamine (PDA) in weak alkaline environment at room temperature. PDA has good biocompatibility, environmental stability and excellent dispersibility in water. Moreover, it can be deposited on the surface of almost all materials to modify them, which not only increases the biomimetic properties of the material surface, but also endows the material surface with abundant functional groups such as amino and hydroxyl groups, greatly improving the activity of the material surface. Therefore, PDA has become a new type of fiber surface modifier. For example, the patent application document CN110258116A discloses a preparation method of polydopamine modified basalt fiber carrier. The basalt fiber after alkali etching and drying is soaked in a dopamine modified solution, placed in a shaking bed at room temperature and shaken, then taken out and dried, to obtain a basalt fiber carrier with abundant surface functional groups, good biocompatibility and hydrophilicity, and promoting the adhesion of microorganisms on its surface, increasing the amount of biofilm and improving the efficiency of wastewater treatment. However, the modified fiber is not suitable for the preparation of PVDF-based composites, because the alkali (NaOH solution) etching will cause damage to the basalt fiber and destroy its performance as a reinforcing body.

[0005] Ag nanowires (AgNWs) commonly used in PVDF-based composites refer to one-dimensional nanomaterials with a diameter usually in the nanometer scale (1-100 nanometers) and a length in the micron or millimeter scale. In PVDF-based composites, Ag nanowires act as fillers, similar to carbon nanotubes, mainly playing the role of improving electromagnetic shielding efficiency. There are few reports in the prior art on silver plating modification of basalt fibers, mainly to cover the fiber surface with a metal (Ag) element with stronger bonding force to increase the fusion with other metal materials. For example, the patent application document CN117701962A discloses a preparation method of basalt fiber reinforced magnesium alloy material, which sequentially roughens, sensitizes, silver-plates and nickel-plates basalt fibers to obtain modified basalt fibers for preparing basalt fiber reinforced magnesium alloy material, achieving the improvement of the high temperature resistance, specific strength and specific modulus of the obtained basalt fiber reinforced magnesium alloy material. Here, the roughening also uses alkali solution to treat the basalt fiber, which damages the surface and cannot guarantee the performance of the PVDF-based composite.

[0006] Fe3O4 has paramagnetism, which can make PVDF-based composite materials obtain low-frequency electromagnetic wave shielding performance. For example, the basalt fiber shielding material and its preparation method and application disclosed in Chinese patent application document CN118185226A disperse basalt fibers in acetone, add a silane coupling agent, then drop nano-silicon dioxide suspension to prepare active fibers; then disperse the active fibers, carbon nanotubes, dopamine, and magnetic Fe3O4 nanoparticles in a buffer solution to prepare a modified solution; finally, drop glutaraldehyde solution into the modified solution to prepare modified basalt fibers with good mechanical properties and electromagnetic shielding performance, which can be well applied in high-voltage test halls. However, in actual production, nanoparticles directly dispersed in the solution are extremely easy to agglomerate, the modification effect is not ideal, and even the modification fails; and the dispersion of Fe3O4 nanoparticles in the solution also easily causes damage to the PVDF polarization process, resulting in a decrease in the piezoelectric performance of the prepared PVDF-based composite material.

[0007] Therefore, how to simultaneously improve the piezoelectric performance and electromagnetic shielding performance of polyvinyl fluoride-based composite materials to meet the needs of modern electronic equipment for wideband electromagnetic protection is still a problem to be solved. SUMMARY

[0008] In view of the above-mentioned problems of existing polyvinyl fluoride (PVDF) -based composite materials, such as the difficulty in synergistically optimizing piezoelectric performance and electromagnetic shielding performance, the present application provides a kind of Ag / Fe3O4 Synergistically Modified Basalt Fiber and PVDF Composite Material and Preparation Method, through Ag Nanoparticle and Fe3O4 Nanoparticle Synergistically Modified Basalt Fiber, through multi-level modification synergistically modified, combined with magnetic field induced orientation process to prepare PVDF-based composite material with high piezoelectric performance and high electromagnetic shielding performance, suitable for flexible electronic devices, aerospace stealth structure and intelligent electromagnetic protection equipment. The specific technical solutions are as follows: Firstly, the present application provides a kind of silver nanoparticle / Fe3O4 Synergistically Modified Basalt Fiber, which includes basalt fiber body and Ag nanoparticle and Fe3O4 nanoparticle modified on its surface.

[0009] The aforementioned silver nanoparticle / Fe3O4 Synergistically Modified Basalt Fiber, the amount of Ag nanoparticle modified on the basalt fiber body is 1.5% to 3.5wt%, and the amount of Fe3O4 nanoparticle modified is 3% to 7wt %; and the mass ratio of the Ag nanoparticle to the Fe3O4 nanoparticle is 1 to 3:1 to 3.

[0010] Secondly, the present application provides a kind of preparation method of the aforementioned modified basalt fiber, including the following steps: 1) Preparation of BF@PDA: after cleaning and drying, basalt fibers were dispersed in dopamine buffer solution, and reacted for 20-30 h; basalt fiber samples were separated by suction filtration at room temperature and cleaned and dried; then the above process was repeated 2-3 times; finally, the polydopamine modified basalt fiber sample was dried and named BF@PDA; 2) Preparation of BF@PDA@Ag: BF@PDA prepared in step 1) was dispersed in anhydrous ethanol, a certain amount of formaldehyde solution was added, and the pH value was adjusted to weak alkaline (between 8.5-9.5), then silver amine solution was added, and stirred under water bath heating conditions for 10-20 min; then, the precipitate was allowed to settle, the solvent was removed, and after multiple washing and drying, the Ag nanoparticle modified basalt fiber sample was obtained, named BF@PDA@Ag; 3) Preparation of BF@PDA@Ag@Fe3O4: BF@PDA@Ag prepared in step 2) was added to PEI solution, ultrasonically dispersed and mixed, and then stirred at room temperature for 10-15 h; then FeCl2·4H2O solution and FeCl3·6H2O solution were added, and the stirring was continued for 20-40 min to form a suspension; then the pH value was adjusted to 11-12 with ammonia water, and the suspension was continued to be stirred at 40-60°C for 20-40 min; finally, centrifugation was performed, the precipitate was washed with deionized water and ethanol for several times, and dried to obtain the Ag nanoparticle and Fe3O4 nanoparticle co-modified basalt fiber sample, named BF@PDA@Ag@Fe3O4, which is a silver nanoparticle / Fe3O4 synergistically modified basalt fiber.

[0011] As a preferred technical solution, in the preparation method of the modified basalt fiber, in step 1), the dopamine buffer solution is a dopamine hydrochloride Tris buffer solution with a concentration of 0.001-0.003 g / mL; the ratio of basalt fiber to dopamine buffer solution is 0.02-0.03 g / mL.

[0012] As a preferred technical solution, in the preparation method of the modified basalt fiber, in step 2), the ratio of BF@PDA to anhydrous ethanol is 0.005-0.02 g / mL; the concentration of the added formaldehyde solution is 0.1-0.5 mol / L, and the amount added is 1 / 10-1 / 2 of the volume of the silver amine solution; the concentration of the silver amine solution is 0.05-0.2 mol / L; the water bath heating temperature is 35-45°C; the standing precipitation time is 1.5-3 h until the fibers are completely settled.

[0013] As a preferred technical solution, in the preparation method of the modified basalt fiber, in step 3), the concentration of the PEI solution is 1-5 mg / mL; the concentration or the liquid concentration ratio of the BF@PDA@Ag dispersed in the PEI solution is 0.005-0.01 g / mL, and the dispersion time is 40-90 min; the concentration of the FeCl2·4H2O solution and the FeCl3·6H2O solution is 0.001-0.003 g / mL, and the volume ratio of the two is 1:2.

[0014] Further, the application provides an oriented PVDF composite material containing the aforementioned silver nanoparticle / ferroferric oxide synergistically modified basalt fiber, the total content of the silver nanoparticle modified basalt fiber and the silver nanoparticle / ferroferric oxide synergistically modified basalt fiber being 5-35 wt% of the mass of PVDF; and the content of the silver nanoparticle modified basalt fiber and the silver nanoparticle / ferroferric oxide synergistically modified basalt fiber being 5-20 wt% of the mass of PVDF, respectively.

[0015] Finally, the application further provides a preparation method of the aforementioned oriented PVDF composite material, comprising the following steps: A) solution blending: adding the modified basalt fiber BF@PDA@Ag modified only with Ag nanoparticles into a PVDF / DMF solution to obtain a suspension A; adding the modified basalt fiber BF@PDA@Ag@Fe3O4 modified with silver ions and Fe3O4 nanoparticles into a PVDF / DMF solution to obtain a suspension B; and mixing the suspension A and the suspension B to obtain a blended suspension required for preparing the PVDF composite material; B) magnetic field directional forming: placing the obtained blended suspension in a vertical magnetic field to induce directional arrangement of BF@PDA@Ag@Fe3O4, simultaneously applying a polarization electric field to activate piezoelectric properties, and then drying to obtain the oriented PVDF composite material.

[0016] As a preferred technical solution, in the preparation method of the aforementioned oriented PVDF composite material, in step A), the mass concentration of the PVDF / DMF solution is 8-12 wt%; the addition amount of BF@PDA@Ag in the suspension A and the addition amount of BF@PDA@Ag@Fe3O4 in the suspension B are both 5-20 wt% of the mass of PVDF; and the blending ratio of the suspension A to the suspension B is 1:1.

[0017] As a preferred technical solution, in the preparation method of the aforementioned oriented PVDF composite material, in step B), the magnetic field directional forming has a directional arrangement inducing time of 35-45 min; the vertical magnetic field strength is 0.5-1.5 T, and the applied polarization electric field strength is 35-45 kV / mm.

[0018] Advantages of the present application: 1) The present application initiatively modifies basalt fiber, and simultaneously modifies Ag nanoparticles and Fe3O4 nanoparticles on the surface of the basalt fiber. The modified basalt fiber not only has good electrical conductivity, but also breaks the limitation of traditional single modification function, and obtains modified basalt fiber with electrically-conductive and magnetically-responsive double functional interface. This makes the application field of basalt fiber leap from traditional structural reinforcing material to electromagnetic shielding, wave absorption and intelligent sensing in high-tech field, and greatly improves the application value and economic value.

[0019] 2) In the basalt fiber modification method of the present application, when polydopamine is used for surface activation of the basalt fiber, the basalt fiber is directly dispersed in a dopamine hydrochloride buffer solution for multiple immersions, without alkali etching or roughening, so as to avoid fiber damage and ensure the strength of the basalt fiber as a PVDF composite material reinforcing body. When the basalt fiber is modified, silver is plated first and then Fe3O4 nanoparticles are modified. The core of this design sequence is to preferentially ensure the conductive foundation of the material, and then superimpose the wave absorption enhancement function to realize synergistic effect. First, a three-dimensional conductive network of silver particles is constructed on the insulating basalt fiber, which lays the foundation for the high-efficiency electric conduction loss and electromagnetic wave reflection ability of the whole material. If this structure is placed on the discontinuous Fe3O4 particle layer, the conductive path will be severely damaged, resulting in a sharp decrease in shielding efficiency. Secondly, the Fe3O4 nanoparticles are used as the outermost layer, and the silver nanoparticles in the inner layer are cleverly constructed into a multilayer mechanism shell of "absorption-reflection-absorption". The incident electromagnetic wave first encounters the Fe3O4 layer with magnetic loss characteristics, part of the energy is absorbed, and the amount of electromagnetic wave penetrating into the interior is reduced due to the improvement of the surface impedance; then the electromagnetic wave is strongly reflected in the silver particle conductive layer in the interior, and the reflected wave is reabsorbed when it passes through the Fe3O4 layer again. This structure not only significantly improves the overall electromagnetic shielding efficiency, but also effectively reduces the secondary electromagnetic pollution by enhancing the absorption mechanism, achieving a perfect balance between reflection and absorption.

[0020] 3) The PVDF composite material prepared by using the modified basalt fiber of the present application not only has excellent mechanical strength and heat resistance, but also the rigid basalt fiber acts as a stress amplifier in the soft PVDF matrix. When the material is subjected to external force, the stress will be concentrated in the interface between the fiber and the matrix, causing the PVDF in this area to produce greater deformation, thereby significantly improving the piezoelectric output (voltage / current). This not only enables the prepared PVDF composite material to simultaneously improve the piezoelectric performance and electromagnetic shielding performance, but also can be directly used as a structural material for equipment shells, cabin bodies, automobiles, etc., to realize self-sensing and self-shielding intelligent structure manufacturing.

[0021] PVDF is a flexible polymer piezoelectric material, and its piezoelectric performance mainly comes from the beta phase in its crystal structure. When the beta phase PVDF is mechanically deformed (stretched or bent), the electric dipoles distributed in its crystal lattice will be oriented and deflected, thereby generating electric charges on the surface of the material and forming voltage / current output. Therefore, under the same external force, the greater and more uneven the strain (deformation) generated inside the PVDF matrix, the higher the piezoelectric output. The modified fiber itself does not produce piezoelectricity, but it creates great strain inhomogeneity. It "focuses" and "amplifies" the macroscopic mechanical force into microscopic giant strain inside the PVDF matrix through its rigidity and firm interface, thereby greatly stimulating the piezoelectric potential of PVDF itself. In addition, the three-dimensional conductive network formed by Ag nanoparticles can serve as an efficient internal electrode, more effectively collecting the charges generated by the beta phase and reducing the loss of charges during transmission.

[0022] (4) The preparation method of the PVDF composite material of the present application mixes the modified basalt fiber with the PVDF / DMF solution, realizes the process reform of "modification first and then compounding", firmly anchors the functional nanomaterials (Ag nanoparticles and Fe3O4 nanoparticles) on the surface of the fiber, instead of directly blending with PVDF, which effectively solves the problem of preventing nanoparticles from being ineffective due to agglomeration, and avoids the destruction of the polarization process of magnetic particles to PVDF, ensuring the full play of the functions of each component. Moreover, the modified basalt fiber not only can form good interfacial adhesion with PVDF / DMF and act as a reinforcing body of the composite material, but also has the dual functions of electrical conductivity and magnetic response, which not only does not sacrifice the piezoelectric performance of the material, but also can improve the piezoelectric performance of the PVDF composite material while improving the electromagnetic shielding performance of the composite material.

[0023] (5) The method for preparing PVDF composite material of the present invention uses basalt fiber modified with silver nanoparticles / Fe3O4 as a skeleton. Through modification treatment, Ag nanoparticles with high conductivity and Fe3O4 with paramagnetism are combined together through the basalt fiber as a carrier. In a directional magnetic field, BF@PDA@Ag@Fe3O4 causes the prepared composite fiber skeleton to be oriented through the paramagnetism of Fe3O4; while BF@PDA@Ag interlocks the oriented fibers, forming a more efficient and continuous conductive path (provided by Ag nanoparticles) in a specific direction, which greatly improves the electromagnetic shielding effectiveness. Simultaneously applied polarized electric field activates the piezoelectric phase function of PVDF. When the material is under pressure, the oriented basalt fibers become concentrated stress transfer points, and the stress is highly concentrated on the PVDF matrix around the fibers, causing greater deformation in this area. This excites a piezoelectric output signal that is much higher than that of disordered composite materials, achieving unexpected results. As a new type of PVDF composite material, it lays the foundation for designing intelligent sensors with orientation recognition capabilities, and has good application prospects and economic value. Attached Figure Description

[0024] Figure 1 These are microscopic images of the unmodified basalt fiber (BF) used in Example 1 of this invention. Figure 2 These are microscopic images of the BF@PDA modified fibers prepared in Example 1 of this invention. Figure 3 These are microscopic images of the BF@PDA@Ag modified fibers prepared in Example 1 of this invention. Figure 4 These are microscopic images of the BF@PDA@Ag@Fe3O4 modified fibers prepared in Example 1 of this invention. Figure 5 The microscopic detection results of the oriented PVDF composite material prepared by the synergistic modification of silver nanoparticles and iron oxide basalt fibers in Example 2 of this invention; Figure 6 The microscopic detection results are shown for the oriented PVDF composite material prepared by the synergistic modification of silver nanoparticles and iron tetroxide with basalt fibers in Comparative Example 4 of this invention. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with embodiments. The basalt fiber used in the following embodiments was purchased from Sichuan Fiberglass Group Co., Ltd., model 502-P1, with a single fiber diameter of 12.7 μm, an average length of 6 mm, and a linear density of 200 tex. Its microstructure is as follows... Figure 1The reagents not provided with sources are all commercially available reagents; the methods not described in detail in the examples are all conventional and well-known experimental methods.

[0026] Example 1 This example is to prepare a basalt fiber modified by silver nanoparticles / magnetite synergistically, which comprises the following steps: 1) Preparation of BF@PDA: first, 0.4 g of Tris was dissolved in 200 mL of deionized water, and the pH of the solution was adjusted to 8.5 with 0.5 mol·L -1 of HCl, and then 0.4 g of dopamine hydrochloride was added to form a dopamine buffer solution. The cleaned and dried basalt fiber (5 g) was added to the dopamine buffer solution and reacted for 24 h; then BF was separated by suction filtration at room temperature, and then washed with deionized water and dried. Then the washed and dried BF was added to the dopamine buffer solution again for reaction, and this repeated immersion was repeated for 3 times, and finally vacuum dried at 40°C for 6 h to obtain a polydopamine modified basalt fiber sample, named BF@PDA, and its microstructure is shown in Figure 2 ; 2) Preparation of BF@PDA@Ag: first, prepare the silver ammine solution. Take 1 g of AgNO3 and add it to 50 ml of deionized water, and then add ~2.5% of dilute ammonia solution dropwise into the AgNO3 aqueous solution while stirring constantly; the solution first appears brownish red precipitate, and then the precipitate disappears, at which point the addition is stopped to obtain the silver ammine solution. Then, carry out the silver mirror reaction. Disperse 1 g of modified BF@PDA in step 1) in 200 ml of anhydrous ethanol, and add 4 ml of formaldehyde solution, while adding a small amount of sodium hydroxide to adjust the pH to weak alkaline (pH about 9). Then add the prepared silver ammine solution, and the mixed solution is reacted in a water bath at 40°C for 15 min with slow stirring (stirring speed 500 rpm). Finally, the silver-plated product is allowed to stand for 2 h to remove the upper solvent, and then deionized water is added, and the washing is repeated for 3 times, and then vacuum dried at 40°C for 6 h to obtain a silver nanoparticle modified basalt fiber sample, named BF@PDA@Ag, and its microstructure is shown in Figure 3 .

[0027] 3) Preparation of BF@PDA@Ag@Fe3O4: Fe3O4 nanoparticles were decorated on the surface of the fiber by a one-pot simplified co-precipitation method. Polyethyleneimine (PEI) solution was chosen as the modification solution system. Through the modification of PEI, the surface of BF@PDA@Ag was changed from a state that is not conducive to the adsorption of iron ions to a positively charged, amino-rich, and sticky surface. This new surface can efficiently capture and immobilize the precursor of Fe3O4 (iron ions) through electrostatic attraction and coordination, laying a solid foundation for the successful preparation of BF@PDA@Ag@Fe3O4 in the next step. Specifically, first, 0.2 g of PEI (molecular weight of 10,000-70,000 g / mol) was dissolved in water to form a PEI solution with a concentration of 2 mg / mL. 0.2 g of BF@PDA@Ag prepared in step 2) was dispersed in the prepared PEI solution and ultrasonicated for 60 min to make it uniformly dispersed. Then, the reaction was stirred at room temperature at a stirring speed of 500 rpm for 12 h. During this period, 0.1 g of FeCl2·4H2O was added to 50 mL of deionized water, and 0.2 g of FeCl3·6H2O was added to 100 mL of deionized water to prepare solutions with a concentration of 0.002 g / mL. After 12 h of reaction of BF@PDA@Ag in the PEI solution, the prepared FeCl2·4H2O solution and FeCl3·6H2O solution were added together to the suspension solution, and the stirring (stirring speed 500 rpm) reaction was continued for 30 min. Then, NH3·H2O was added to adjust the pH value to 11-12, and the suspension was further co-precipitated at 50°C for 30 min with the stirring speed unchanged. Finally, the dark precipitate was separated by centrifugation and washed with deionized water and ethanol for 3 times, and then vacuum dried at 40°C for 6 h to obtain the basalt fiber modified with silver nanoparticles / magnetite, named BF@PDA@Ag@Fe3O4, and its microstructure is shown in Figure 4

[0028] Example 2 This example is to prepare an oriented PVDF composite material, which includes the following steps: ​A) Solution blending: First, a 10wt% concentration of PVDF / DMF solution 1000 mL was prepared, and was stirred at 400 rpm until a transparent and uniform solution was formed, which was then divided into two equal parts. The BF@PDA@Ag prepared in Example 1 (10wt% of the mass of PVDF) was added to one of the PVDF / DMF solutions, and was ultrasonically dispersed at 60°C for 2h to obtain suspension A; at the same time, the BF@PDA@Ag@Fe3O4 prepared in Example 1 (10wt% of the mass of PVDF) was added to the other PVDF / DMF solution, and was ultrasonically dispersed at 60°C for 2h to obtain suspension B; then, the suspension A and the suspension B were mixed to obtain the blending suspension (blending ratio 1:1) required for preparing the PVDF composite material.

[0029] B) Magnetic field oriented forming: the blending suspension obtained in step A) was placed in a 1.0T vertical magnetic field to induce the directional arrangement of BF@PDA@Ag@Fe3O4, and a 40kV / mm polarization electric field was applied to activate the piezoelectric phase function of PVDF, and the treatment was performed for 30min, and finally dried at 60°C to obtain the oriented PVDF composite material, which is denoted as the composite material of the application, and the microstructure thereof is shown in Figure 5 .

[0030] Comparative Example 1: PVDF composite material prepared by using unmodified BF In this example, a PVDF composite material was prepared by the following method: first, a 10wt% concentration of PVDF / DMF solution was prepared, and was stirred at 400 rpm until a transparent and uniform solution was formed, then 20% basalt fiber of the mass of PVDF was added to the PVDF / DMF solution, and was ultrasonically dispersed at 60°C for 2h to obtain a suspension; then, the suspension was placed in a 1.0T vertical magnetic field, and a 40kV / mm polarization electric field was applied; finally, the PVDF material was dried at 60°C to obtain the comparative composite material 1.

[0031] Comparative Example 2: PVDF composite material prepared by adding only BF@PDA@Ag In this example, an Ag nanoparticle modified basalt fiber PVDF composite material was prepared by the following method: first, a 10wt% concentration of PVDF / DMF solution was prepared, and was stirred at 400 rpm until a transparent and uniform solution was formed, then 20% BF@PDA@Ag prepared in Example 1 of the mass of PVDF was added to the PVDF / DMF solution, and was ultrasonically dispersed at 60°C for 2h to obtain a suspension, then the suspension was placed in a 1.0T vertical magnetic field, and a 40kV / mm polarization electric field was applied; finally, the PVDF material was dried at 60°C to obtain the comparative composite material 2.

[0032] Comparative Example 3: PVDF composite material prepared by adding only BF@PDA@Ag@Fe3O4 The present embodiment is to prepare an Ag nanoparticle and ferroferric oxide modified basalt fiber PVDF composite. The preparation method is as follows: first, prepare a 10wt% PVDF / DMF solution, and magnetically stir at a speed of 400 rpm until a transparent and uniform solution is formed. Then, add the BF@PDA@Ag@Fe3O4 (20% of the mass of PVDF) prepared in Example 1 to the PVDF / DMF solution, and ultrasonically disperse at 60°C for 2h to obtain a suspension. Then, place the suspension in a 1.0T vertical magnetic field, and apply a polarization electric field of 40kV / mm at the same time. Finally, dry at 60°C to obtain a PVDF material, which is denoted as Comparative Composite 3.

[0033] Comparative Example 4: No magnetic field orientation The present embodiment is also to prepare a PVDF composite. The preparation method is the same as that of Example 2, but the magnetic field orientation forming step is not performed. That is, after mixing the suspension A and the suspension B, directly dry at 60°C to obtain an oriented PVDF composite, which is denoted as Comparative Composite 4. The microstructure thereof is shown in Figure 6 .

[0034] Effect Example 1 The present effect example is to investigate the piezoelectric properties (PE) and electromagnetic shielding properties (SE) of the composite 1 prepared in Example 2 and the comparative composites 1-4 prepared in Comparative Examples 1-4.

[0035] In the present embodiment, the conductivity, electromagnetic shielding, tensile properties, open-circuit voltage, and short-circuit current of each PVDF composite are used as evaluation criteria.

[0036] Test method: (1) Conductivity A direct current resistance tester is used to test each sample (sheet-shaped sample 10mm*20mm*2mm, prepared by a hot press, hot press temperature 190°C, hot press time 5min, hot press pressure 20 MPa) at room temperature. To reduce errors, each sample is tested 10 times, and then the maximum and minimum values are removed, and the average of the remaining data results is taken. The volume resistivity and conductivity calculation formulas are as follows: (1-1), (1-2); Wherein, p is the volume resistivity of the material; R is the measured value of the sample resistance; h is the cross-sectional width of the measured sample; d is the cross-sectional thickness of the sample; L is the distance between the two electrodes; and σ is the conductivity.

[0037] (2) Electromagnetic shielding performance The EMI shielding performance was tested by the coaxial method in the frequency range of 8.2-12.4 GHz (X-band) according to the ASTM ES7-83 standard using a vector network analyzer (R&S ZNB20). The sample size was 20 mm x 20 mm x 2 mm (cut after hot-pressing sheet). The scattering parameters (S11 and S21), also known as S-parameters, were obtained directly from the vector network analyzer, from which the power coefficients of the absorption coefficient (A), the reflection coefficient (R), and the transmission coefficient (T), as well as the total SE (SET), the absorption SE (SEA), and the reflection SE (SER) values were calculated by the following equations: (2-1), (2-2), (2-3); (1-R) is defined as the signal strength of the incident electromagnetic wave that enters the interior of the shielding material after reflection.

[0038] The effective absorption rate Aeff is: (2-4); According to the definition of shielding effectiveness, the reflection shielding effectiveness and the absorption shielding effectiveness can be obtained as: (2-5), (2-6); When SEA > 10 dB, the multiple reflection loss can be ignored, and thus the total shielding effectiveness can be expressed as: (2-7); (3) Tensile properties The tensile strength was tested at room temperature according to the GB / T 528-2009 test standard.

[0039] (4) Open-circuit voltage, short-circuit current The samples were first cut into 5 cm x 5 cm square specimens and firmly pasted on rigid acrylic (PMMA) substrates to prevent bending deformation during the test. A PMMA plate of the same material was chosen as the moving layer, and the two friction layers were connected by a polyimide film to precisely control the test height and ensure structural stability. During the device assembly process, copper wires were connected to the two electrode layers, respectively, and the other end was connected to the positive probe of the electrometer to monitor the electrical output in real time. Finally, the output performance of the materials was systematically evaluated under different operating conditions (working frequency: 1-4 Hz; contact pressure: 4-16 kPa) using a vertical mode friction nanogenerator test platform to evaluate their energy harvesting efficiency and stability. The test results are shown in Table 1.

[0040] Table 1. Test results of piezoelectric properties and electromagnetic shielding properties of various PVDF composite materials

[0041] From the test results in Table 1, it can be seen that the comparative composite 1 prepared by using unmodified BF has no shielding performance and poor piezoelectric performance, and the improvement of the mechanical properties of PVDF is also weak due to the random arrangement of the internal fibers. Compared with the comparative composite 1 adding unmodified BF, the electromagnetic shielding efficiency of the materials is improved in the comparative composite 2 adding BF@PDA@Ag modified fibers and the comparative composite 3 adding BF@PDA@Ag@Fe3O4 modified fibers, but the electromagnetic shielding effect of the comparative composite 3 adding BF@PDA@Ag@Fe3O4 modified fibers is obviously better than that of the comparative composite 2 adding BF@PDA@Ag modified fibers, which indicates that the BF surface is grafted with Ag to change BF from an insulating material to a conductive material, and the modification of Fe3O4 is mainly to obtain a high-efficiency absorption electromagnetic shielding material to prevent secondary pollution of electromagnetic waves, so that the addition of BF@PDA@Ag@Fe3O4 modified fibers can better absorb the electromagnetic waves on the surface of the composite and improve the electromagnetic shielding efficiency of the material. However, the electromagnetic shielding efficiency of the composite (the composite of the application) adding BF@PDA@Ag modified fibers and BF@PDA@Ag@Fe3O4 modified fibers at the same time is better than that of the composite adding BF@PDA@Ag@Fe3O4 modified fibers alone. Moreover, the composite of the application also has a significant improvement in the electrical conductivity, open-circuit voltage and short-circuit current compared with the comparative composite 2 and the comparative composite 3, which indicates that the addition of BF@PDA@Ag modified fibers and BF@PDA@Ag@Fe3O4 modified fibers at the same time can effectively improve the electromagnetic shielding efficiency of the composite and strengthen the piezoelectric performance of the composite, realizing a "win-win" situation. Compared with the comparative composite 4, the BF@PDA@Ag@Fe3O4 modified fibers cannot be oriented and are still in a random arrangement state due to the absence of a magnetic field for directional forming, so the mechanical properties of the comparative composite 4 are relatively weak, while the mechanical properties of the composite of the application are better. In addition, compared with the test results of the composite of the application and the comparative composite 4, it can be seen that the application of a magnetic field for directional forming and high-voltage polarization is a necessary means to simultaneously improve the electromagnetic shielding efficiency and piezoelectric performance of the composite, and can further improve the tensile strength of the composite. Therefore, the composite of the application has excellent comprehensive properties such as mechanical properties, electromagnetic shielding performance and piezoelectric performance.

[0042] Example 2 This example is to investigate the influence of the addition amount of silver nanoparticle / ferroferric oxide synergistically modified basalt fiber and the ratio of BF@PDA@Ag and BF@PDA@Ag@Fe3O4 (g) on the properties of the prepared PVDF composite.

[0043] This example is based on the preparation method of Example 2, except that the amount of silver nanoparticles / ferriferrous oxide synergistically modified basalt fiber added and the ratio of BF@PDA@Ag and BF@PDA@Ag@Fe3O4(g) are different. The remaining components and preparation methods are consistent with those in Example 2. In this example, the conductivity, electromagnetic shielding, tensile properties, and open-circuit voltage, short-circuit current of the prepared PVDF composite materials are also used as evaluation criteria. The results are shown in Table 2.

[0044] Table 2. Amount of modified basalt fiber in PVDF composite and performance

[0045] The results of Table 2 show that as the amount of BF@PDA@Ag modified fiber and / or BF@PDA@Ag@Fe3O4 modified fiber increases, the conductivity, electromagnetic shielding effectiveness, mechanical properties, and piezoelectric properties of the composite material are all improved. And as the amount of BF@PDA@Ag@Fe3O4 modified fiber increases, the absorption coefficient A of the material is higher, i.e. the surface electromagnetic wave is less reflected, and the absorption performance of the shielding material is better. However, as the amount of modified fiber increases, the tensile strength of the composite material first increases and then decreases, reaching a maximum when the total amount of BF@PDA@Ag modified fiber and / or BF@PDA@Ag@Fe3O4 modified fiber reaches 20%. This is because excessive filler addition will cause fiber aggregation, resulting in a decrease in mechanical properties. Therefore, it is recommended that the total amount of BF@PDA@Ag modified fiber and / or BF@PDA@Ag@Fe3O4 modified fiber in the PVDF composite material not exceed 35% of the weight of PVDF, and the amount of BF@PDA@Ag and BF@PDA@Ag@Fe3O4 added should be controlled at 5-20wt% of the mass of PVDF. In summary, Formula 6 (Example 2) has more excellent comprehensive performance, i.e. mechanical properties, high absorption electromagnetic shielding, and piezoelectric properties.

[0046] In summary, the present application breaks the limitation of traditional single modification function, initiatively carries out synergistic modification on basalt fiber, simultaneously modifies Ag nanoparticles and Fe3O4 nanoparticles on the surface of the basalt fiber, so that the modified basalt fiber not only has good conductivity, but also obtains modified basalt fiber with conductive-magnetic response dual functional interface, which makes the application field of basalt fiber leap from traditional structural reinforcing material to electromagnetic shielding, wave absorption and intelligent sensing in high-tech field, greatly improving its application value and economic value. When the basalt fiber is surface-activated by polydopamine in the basalt fiber modification method of the present application, the basalt fiber is directly dispersed in a dopamine hydrochloride buffer solution for multiple infiltration, without alkali etching or roughening, so as to avoid fiber damage and ensure the strength of the basalt fiber as a PVDF composite material reinforcing body; when the basalt fiber is modified, silver plating is carried out first and then Fe3O4 nanoparticles are modified, and the core of this design sequence is to preferentially ensure the conductive foundation of the material, and then superimpose the wave absorption enhancement function to realize synergistic effect. The PVDF composite material prepared by using the modified basalt fiber of the present application not only endows the composite material with excellent mechanical strength and heat resistance, but also makes the rigid basalt fiber act as a stress amplifier in the soft PVDF matrix, so that when the material is subjected to external force, the stress will be concentrated in the interface between the fiber and the matrix, causing the PVDF in this area to produce greater deformation, thereby significantly improving its piezoelectric output (voltage / current). This not only enables the prepared PVDF composite material to realize synchronous improvement of piezoelectric performance and electromagnetic shielding performance, but also can be directly used as a structural material for equipment shells, cabin bodies, automobiles, etc., to realize intelligent structure manufacturing with self-sensing and self-shielding, and has good application prospect and economic value.

[0047] It is apparent for those skilled in the art that the present application is not limited to the details of the above-described exemplary embodiments, but can be implemented in other concrete forms without departing from the spirit or essential characteristics of the present application. Therefore, the embodiments should be considered in all aspects as exemplary and non-limiting. Furthermore, it should be understood that although the present specification is described in terms of embodiments, it does not contain only one technical solution, and the description manner of the specification is only for the sake of clarity, and those skilled in the art should consider the specification as a whole, and the technical solutions in the embodiments can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A basalt fiber synergistically modified with silver nanoparticles and iron oxide, characterized in that: The modified basalt fiber includes a basalt fiber body and Ag nanoparticles and Fe3O4 nanoparticles modified on its surface. The amount of modified Ag nanoparticles is 1.5% to 3.5 wt% of the bulk mass of Wuyan fiber, and the amount of modified Fe3O4 nanoparticles is 3% to 7 wt% of the bulk mass of Wuyan fiber; and the mass ratio of Ag nanoparticles to Fe3O4 nanoparticles is 1 to 3: 1 to 3.

2. A method for preparing the modified basalt fiber according to claim 1, characterized in that: Includes the following steps: 1) Preparation of BF@PDA: The cleaned and dried basalt fibers were dispersed in a dopamine buffer solution and reacted for 20-30 h; the basalt fiber sample was separated by filtration at room temperature, and then cleaned and dried; the above process was repeated 2-3 times; finally, the polydopamine-modified basalt fiber sample was obtained by drying and named BF@PDA. 2) Preparation of BF@PDA@Ag: The BF@PDA prepared in step 1) was dispersed in anhydrous ethanol, a certain amount of formaldehyde solution was added, and the pH value was adjusted to between 8.5 and 9.

5. Then, silver ammonia solution was added, and the reaction was stirred for 10 to 20 minutes under water bath heating conditions. Then, the mixture was allowed to stand to precipitate, the solvent was removed, and the mixture was washed several times and dried to obtain the basalt fiber sample modified with Ag nanoparticles, which was named BF@PDA@Ag. 3) Preparation of BF@PDA@Ag@Fe3O4: The BF@PDA@Ag prepared in step 2) was added to PEI solution, ultrasonically dispersed and mixed, and then stirred at room temperature for 10-15 h. Then FeCl2·4H2O solution and FeCl3·6H2O solution were added, and the mixture was stirred for another 20-40 min to form a suspension. The pH was then adjusted to 11-12 with ammonia water, and the suspension was stirred at 40-60°C for another 20-40 min to co-precipitate. Finally, the mixture was centrifuged, and the precipitate was washed several times with deionized water and ethanol. After drying, a basalt fiber sample modified with Ag nanoparticles and Fe3O4 nanoparticles was obtained and named BF@PDA@Ag@Fe3O4, which is a basalt fiber synergistically modified with silver nanoparticles and iron tetroxide.

3. The method for preparing modified basalt fiber according to claim 2, characterized in that: In step 1), The dopamine buffer solution is a dopamine hydrochloride Tris buffer solution with a concentration of 0.001–0.003 g / mL; The feed-to-liquid ratio of basalt fibers dispersed in dopamine buffer solution is 0.02–0.03 g / mL.

4. The method for preparing modified basalt fiber according to claim 2, characterized in that: In step 2), The material-to-liquid ratio of BF@PDA dispersed in anhydrous ethanol is 0.005–0.02 g / mL; The concentration of the added formaldehyde solution is 0.1–0.5 mol / L, and the amount added is 1 / 10 to 1 / 2 of the volume of the silver ammonia solution. The concentration of the silver ammonia solution is 0.05–0.2 mol / L; The water bath heating temperature is 35–45℃; The settling time is 1.5 to 3 hours, until the fibers are completely settled.

5. The method for preparing modified basalt fiber according to claim 3, characterized in that: In step 3), The concentration of the PEI solution is 1–5 mg / mL; The concentration or material-to-liquid ratio of BF@PDA@Ag dispersed in PEI solution is 0.005–0.01 g / mL, and the dispersion time is 40–90 min. The concentrations of the FeCl2·4H2O solution and the FeCl3·6H2O solution are both 0.001–0.003 g / mL, and the volume ratio of the two solutions is 1:

2.

6. An oriented PVDF composite material, characterized in that: The PVDF composite material contains basalt fibers modified with silver nanoparticles and basalt fibers modified with silver nanoparticles / Fe3O4 as described in claim 1, and the content of both the silver nanoparticle-modified basalt fibers and the silver nanoparticle / Fe3O4-modified basalt fibers is 5 to 20 wt% of the mass of PVDF.

7. The oriented PVDF composite material according to claim 6, characterized in that: In this PVDF composite material, the total content of silver nanoparticle-modified basalt fiber and silver nanoparticle / ferric oxide synergistic modified basalt fiber is 5-35 wt% of the PVDF mass.

8. A method for preparing the oriented PVDF composite material according to claim 6 or 7, characterized in that: Includes the following steps: A) Solution blending: Modified basalt fibers BF@PDA@Ag modified only with Ag nanoparticles were added to a PVDF / DMF solution to obtain suspension A; modified basalt fibers BF@PDA@Ag@Fe3O4 modified with silver ions and Fe3O4 nanoparticles were added to a PVDF / DMF solution to obtain suspension B; suspension A and suspension B were mixed to obtain the blended suspension required for preparing PVDF composite materials; B) Magnetic field orientation molding: The obtained blend suspension is placed in a vertical magnetic field to induce the directional alignment of BF@PDA@Ag@Fe3O4. At the same time, a polarizing electric field is applied to activate the piezoelectric properties. After drying, the oriented PVDF composite material can be obtained.

9. The method for preparing the oriented PVDF composite material according to claim 8, characterized in that: In step A), The mass concentration of the PVDF / DMF solution is 8–12 wt%. The amount of BF@PDA@Ag added to suspension A and the amount of BF@PDA@Ag@Fe3O4 added to suspension B are both 5-20 wt% of the PVDF mass. The ratio of suspension A to suspension B is 1:

1.

10. The method for preparing the oriented PVDF composite material according to claim 8, characterized in that: In step B), the magnetic field orientation shaping is performed, the strength of the vertical magnetic field is 0.5 to 1.5T, the induction orientation alignment time is 35 to 45 minutes, and the applied polarization electric field strength is 35 to 45 kV / mm.

Citation Information

Patent Citations

  • Preparation method of polydopamine modified basalt fiber carrier

    CN110258116A

  • Preparation method of basalt fiber reinforced magnesium alloy material

    CN117701962A

  • Basalt fiber shielding material and preparation method and application thereof

    CN118185226A

  • BAS basalt fiber reinforced antibacterial composite pipe

    CN116285134A

  • Multi-layer alternate basalt fiber / resin electromagnetic shielding composite material and preparation method thereof

    CN118664995A

Cited By

  • Basalt fiber composite material with self-healing performance and preparation method thereof

    CN121492251A